CAD/CAM scaffolds for bone tissue engineering: investigation of biocompatibility of selective laser melted lightweight titanium. Issue 7 (14th July 2020) - Naujokat, Hendrik; Rohwedder, Johanna; Gülses, Aydin; Cenk Aktas, Oral; Wiltfang, Jörg; Açil, Yahya
Abstract : The objective of the current in‐vitro study was to evaluate the biocompatibility of a new type of CAD/CAM scaffold for bone tissue engineering by using human cells. Porous lightweight titanium scaffolds and Bio‐Oss® scaffolds as well as their eluates were used for incubation with human osteoblasts, fibroblasts and osteosarcoma cells. The cell viability was assessed by using fluorescein diazo‐acetate propidium iodide staining. Cell proliferation and metabolism was examined by using MTT‐, WST‐Test and BrdU‐ELISA tests. Scanning electron microscope was used for investigation of the cell adhesion behaviour. The number of devitalised cells in all treatment groups did not significantly deviate from the control group. According to MTT and WST results, the number of metabolically active cells was decreased by the eluates of both test groups with a more pronounced impact of the eluate from Bio‐Oss®. The proliferation of the cells was inhibited by the addition of the eluates. Both scaffolds showed a partial surface coverage after 1 week and an extensive to complete coverage after 3 weeks. The CAD/CAM titanium scaffolds showed favourable biocompatibility compared to Bio‐Oss® scaffolds in vitro. The opportunity of a defect‐specific design and rapid prototyping by selective laser melting are relevant advantages in the field of bone tissue engineering and regenerative medicine.